Phytosterols: From Preclinical Evidence to Potential Clinical Applications - Salehi, Bahare; Quispe, Cristina; Sharifi-Rad, Javad; Cruz-Martins, Natália; Nigam, Manisha; Mishra, Abhay Prakash; Konovalov, Dmitryi Alexeevich; Orobinskaya, Valeriya; Abu-Reidah, Ibrahim M.; Zam, Wissam; Sharopov, Farukh; Venneri, Tommaso; et al. (Frontiers in Pharmacology, 2021)
Phytosterols (PSs) are plant-originated steroids. Over 250 PSs have been isolated, and each plant species contains a characteristic phytosterol composition. A wide number of studies have reported remarkable pharmacological effects of PSs, acting as chemo-preventive, anti-inflammatory, antioxidant, antidiabetic, and anti-atherosclerotic agents. However, PS bioavailability is a key issue, as it can be influenced by several factors (type, source, processing, preparation, delivery method, food matrix, dose, time of administration into the body, and genetic factors), and the existence of a close relationship between their chemical structures (e.g., saturation degree and side chain length) and low absorption rates has been stated. In this sense, the present review intends to provide in-depth data on PS therapeutic potential for human health, also emphasizing their pre-clinical effects and bioavailability-related issues.